Effects of biotic stress caused by Potato virus Y on photosynthesis in ipt transgenic and control Nicotiana tabacum L - Synková, Helena; Semorádová, Šárka; Schnablová, Renáta; Müller, Karel; Pospíšilová, Jana; Ryšlavá, Helena; Malbeck, Jiří; Čeřovská, Noemi (Plant science (Limerick), 2006)
We studied the effect of biotic stress caused by Potato virus Y NTN (PVY) on photosynthesis in transgenic P ssu- ipt tobacco overproducing endogenous cytokinins (CK) in comparison with control (non-transformed) plants. Both control and transgenic tobacco were grown as rooted or grafted plants. Content of viral protein increased significantly in control tobacco within ca. 18 days after inoculation, whereas transgenic plants exhibited much lower accumulation. This corresponded also with the presence of visible symptoms of PVY infection; while they were always present in control, rooted tobacco, they never developed in transgenic grafts. Contents of CKs (mostly in the forms of N- and/or O-glucosides) increased in all infected plants except transgenic grafts, where the highest amount of CKs was found already prior the inoculation. The photosynthetic rate ( P N) was significantly inhibited by PVY infection in control and transgenic rooted plants, while both grafted types were less affected. Reduction of P N was caused not only by stomata closure, but also by the decrease of ribulose-1,5-bisphosphate carboxylase/oxygenase activity, contents of chlorophylls and xanthophyll cycle pigments, and activity of photosystem II (PSII). The negative effect on PS II was promoted by high irradiance treatment particularly in both rooted types infected by PVY.